Surgical management of congenital heart disease I : complex transposition of great arteries // right and left ventricular outflow tract obstruction // Ebstein´s Anomaly // a video manual - Hraska, Viktor (Springer Berlin Heidelberg, 2012)
Approximately 120 different surgical procedures are used to correct congenital heart diseases, and the burden that this places on the surgeon is compounded by the exceptional complexity of the techniques and the rarity of many of the lesions. Training is problematic, not least because of legal issues, and currently available texts, drawings, and images are no substitute for real 'live' surgery. Against this background, the authors have set out to create an interactive multimedia manual that covers many aspects of congenital heart surgery. Each heart defect is addressed in an individual chapter, elaborating specific surgical anatomy and indication for surgery of heart defect first, followed by video clips depicting the operative approach and technique. The clips are accompanied by a clear descriptive narrative, and patient history and diagnostic images are available to provide a clear backdrop to the operation. The chosen format makes this manual not only a very powerful teaching tool for practicing cardiac surgeons and surgeons in training but also a valuable source of information for related services such as pediatric and adult cardiologists, cardiac anesthesiologist, cardiac intensivists, perfusionists and medical students.